The Digital Infrastructure of Intimacy (Seminar_BG, 2025)
The paper presents findings from an empirical study of the ways in which young people appropriate digital space for the purposes of their intimate experiences. The theme of intimate relationships is traced from two perspectives: through the places where they occur (a kind of topography of digital space for everyday use is made, and different territories are conceptualized as arenas of intimacy) and through the specific rituals of intimacy, which respondents conceive through symbolic forms of recognition (e.g. public digital disclosure of the fact of commitment) or symbolic forms of violence (e.g. digital humiliation as a result of jealousy or relationship termination). I define digital arenas and on-stage intimacy as a type of public intimacy specific to the digital space, where the private is made public to specific audiences in order to better understand and appreciate the self and the self in relationship, incorporating the reactions (imagined or real) of others to achieve a richer and more intense sense of intimacy.  ReferencesAlberoni, F. 1981. Le choc amoureux. Paris: Ramsay.Bevan, J. L. 2013. The Communication of Jealousy. New York: Peter Lang.Boyd, D. 2014. It’s Complicated. New Haven and London : Yale Yniversity Press.Brody, N., LeFebvre, L. E, Blackburn, K. G. 2017. "Post-Dissolution. Surveillance on Social Networking Sites", In: Punyanunt-Carter, N. M., Wrench, J. S. (Eds.). The Impact of Social Media in Modern Romantic Relationships. London: Lexington Books, 237-257.Casilli, A. 2010. Les liaisons numériques. Vers une nouvelle sociabilité?. Paris: Seuil.Fox, J., Warber, K. M., Makstaller, D. C. 2013. "The Role of Facebook in Romantic Relationship Development: An Exploration of Knapp’s Relational Stage Model". Journal of Social and Personal Relationships, 30, 771-794.Fox, J., Warber, K. M. 2013. "Romantic Relationship Development in the Age of Facebook: An Exploratory Study of Emerging Adults’ Perceptions, Motives and Behaviors". Cyberpsychology, Behavior, and Social Networking, 16–1, 3-7.Georgiev, E., Kanchev, P., Haydinyak, M., Apostolov, G. 2016. Roditelska podkrepa za razvitie na digitalnite umenia na detsata. Natsionalno predstavitelno izsledvane „Detsata na Bulgaria onlayn“. https://www.safenet.bg/wp-content/uploads/2015/05/parental-support-bg4.pdf. (last seen 27.06.2025)Goffman, E. 2000 [1956]. Predstavyaneto na Az-a vav vsekidnevieto [The Presentation of Self in Everyday Life (Bulgarian translation)]. Sofia: Izdatelska kashta „Petar Beron“.Jansson, A. 2013. "Mediatization and Social Space: Reconstructing Mediatization for the Transmedia Age". Communication Theory, 23, 279-296.Katz, J. E., Aakhus, M. (Eds.). 2002. Perpetual Contact: Mobile Communication, Private Talk, Public Performance. Cambridge: Cambridge University Press.Knobloch, L. K., Donovan-Kicken, E. 2006. "Perceived Involvement of Network Members in Courtships: A Test of the Relational Turbulence Model". Personal Relationships, 13 –3, 281-302.LeFebvre, L. E. 2017. "Phantom Lovers. Ghosting as a Relationship Dissolution Strategy in the Technological Age". In: Punyanunt-Carter, N. M., Wrench, J. S. (Eds.). The Impact of Social Media in Modern Romantic Relationships. London: Lexington Books, 219-235.Lejealle, Catherine. 2014. "On publie moins sur Facebook quand on est amoureux : les 3 phases du célibat à 'en couple'”. Leplus.nouvelobs.com. 17.02.2014, (Last seen 06.12.2024).Licoppe, Ch. 2012. "Understanding mediated appearances and their proliferation: The case of the phone rings and the 'crisis of the summons". New Media & Society, 14 –7, 1073-1091.Marwick, A. E., Boyd, D. 2014. “'It’s just drama': Teen perspectives on conflict and aggression in a networked era". Journal of Youth Studies, 17, 1187–1204.Neykova, N. 2015. Mobilni fantasmagorii. Telefonno vaobrazhaemo i mladezhki telekulturi. Sofia: Fondatsia Mediyna demokratsia.Neuburger, R. 2000. Les territoires de l'intime. L'individu, le couple, la famille. Paris: Odile Jacob.Paasonen, S. 2017. "Infrastructures of intimacy". In: Andreassen, R., Petersen, M. N., Harrison, K., Raun, T. (Eds.). Mediated Intimacies: Connectivities, Relationalities and Proximities. London: Routledge, 103-116.Petrova, S. 2018. "Strategii za spravyane s 'izlishnite' obrazi: Snapchat". Piron, 15.Poltash, N. 2013. "Snapchat and Sexting: A Snapshot of Baring Your Bare Essentials". Law School Journals. JOLT, 19-4.Ragouet, P. 2000. "Notoriété professionnelle et organisation scientifique". Cahiers internationaux de sociologie, 109, 317-341.Ruppel, E. K. 2015. "The Affordance Utilization Model: Communication Technology Use as Relationships Develop". Marriage and Family Review, 51, 669-686.Yang, Ch.-Ch., Brown, B. B., Braun, M. 2014. "From Facebook to cell calls: Layers of electronic intimacy in college students’ interpersonal relationships". New Media & Society, 16 –1, 5-23.
Keywords: digital love and intimacy; social networks; intimacy on stage; arenas of intimacy; digital ritualization of intimate relationship